Clinical simulation in Australia and New Zealand: Through the lens of an advisory group - Brown, R.; Guinea, S.; Crookes, P.; McAllister, M.; Levett-Jones, T.; Kelly, Michelle; Reid-Searl, K.; Churchouse, C.; Andersen, P.; Chong, N.; Smith, Andrew (Elsevier BV, 2012)
Across Australia, innovations in simulation to enhance learning in nursing have been occurring for three decades and nursing is, and needs to be, a leading player in simulation knowledge diffusion. However, expertise is unevenly distributed across health services and education providers. Rather than build on the expertise and achievements of others, there is a tendency for resource duplication and for trial and error problem solving, in part related to a failure to communicate achievements for the benefits of the professional collective. For nursing to become a leader in the use of simulation and drive ongoing development, as well as conducting high quality research and evaluation, academics need to collaborate, aggregate best practice in simulation learning, and disseminate that knowledge to educators working in health services and higher education sectors across the whole of Australia and New Zealand. To achieve this strategic intent, capacity development principles and committed action are necessary. In mid 2010 the opportunity to bring together nurse educators with simulation learning expertise within Australia and New Zealand became a reality. The Council of Deans of Nursing and Midwifery (CDNM) Australia and New Zealand decided to establish an expert reference group to reflect on the state of Australian nursing simulation, to pool expertise and to plan ways to share best practice knowledge on simulation more widely. This paper reflects on the achievements of the first 18 months since the group's establishment and considers future directions for the enhancement of simulation learning practice, research and development in Australian nursing.